Intersectional Approach by Youth Feminist Activism “Girl Up” in Spreading Gender Equality Values in Southeast Asia (Indonesia, the Philippines, and Vietnam) - Lisa Angelina Putri Purnamasari*; Neneng Konety (Universitas Syiah Kuala, 2023)
The feminist movement led by adolescent girls constitutes a new type of social movement striving for a revolution of anti-patriarchy society. This type of new social movement centers on instilling gender equality values at the grassroots level by promoting gender mainstreaming in every aspect of society. Guided by an intersectional feminist approach, Girl Up as a global initiative, adopts an inclusive approach that acknowledges the multifaceted struggles faced by girls, women, and marginalized communities with varying identities. This study seeks to elucidate the role of Girl Up in Southeast Asia, specifically in Indonesia, the Philippines, and Vietnam, in disseminating gender equality values through an intersectional feminist approach. The research draws upon the concepts of New Social Movement, Intersectional Feminism, and the